Cone Beam CT of the Head and Neck An Anatomical Atlas - Kau, Chung H.; Abramovitch, Kenneth; Kamel, Sherif Galal; Bozic, Marko; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
'Cone Beam CT of the Head and Neck' presents normal anatomy of the head using photographs of cadavers and CBCT images in sagittal, axial and coronal planes with the anatomic structures and landmarks clearly labelled. Important structures and regions are presented in detailed view. This is the first book with photographs of human tissue (based on slicing of cadaveric heads) combined with CBCT images.
Introduction -- Conventional Computed Tomography (CT) -- CBCT -- CBCT Acquisition Systems -- Uses of CBCT Technology -- Axial -- Coronal -- Sagittal.
Keywords: Dentistry; Human anatomy; Radiology, Medical; Neurosurgery; Surgery; Dentistry; Dentistry; Oral and Maxillofacial Surgery; Imaging / Radiology; Anatomy; Plastic Surgery; Neurosurgery